2007
DOI: 10.3748/wjg.v13.i42.5598
|View full text |Cite
|
Sign up to set email alerts
|

Pouchitis

Abstract: While restorative proctocolectomy with ileal pouch-anal anastomosis has significantly improved the quality of life in patients with underlying ulcerative colitis who require surgery, complications can occur. Pouchitis as the most common long-term complication represents a spectrum of disease processes ranging from acute, antibioticresponsive type to chronic antibiotic-refractory entity. Accurate diagnosis using a combined assessment of symptoms, endoscopy and histology and the stratification of clinical phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…The most popular present theory explains pouchitis as a recurrence of ulcerative colitis [20]. This is supported by the fact that in the 2 conditions the changes in the intestinal mucosa have a similar endoscopic and microscopic picture, as well as similar immunology, with the activation of the same pro-inflammatory cytokines and a similar response to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The most popular present theory explains pouchitis as a recurrence of ulcerative colitis [20]. This is supported by the fact that in the 2 conditions the changes in the intestinal mucosa have a similar endoscopic and microscopic picture, as well as similar immunology, with the activation of the same pro-inflammatory cytokines and a similar response to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 49%
“…Inflammation of the intestinal pouch -"pouchitis" -is the most common late complication of restorative proctocolectomy and its prevalence increases with the passage of time after ileostomy closure. It is currently believed that about 50% of patients operated on for ulcerative colitis will experience at least one episode of pouchitis [20]. Chronic inflammation is seen in 10-15% of intestinal pouches [21].…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [19] stated that this inherent discrepancy among studies may be associated with the following factors: sample size, numbers of variables and outcomes, type of statistical analysis, diagnostic criteria for pouchitis, classification of pouchitis (acute vs. chronic entities), and type of controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports revealed that a course of antibiotic-responsive pouchitis could evolve into antibiotic-dependent pouchitis followed by antibiotic-refractory pouchitis, and pouchitis subtypes were shown to change during follow-up [19,20]. Pouchitis encompasses a variety of disease processes that can change over time, which makes identification of predictive factors for this condition difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime risk for colectomy surgery is 70%-80% for Crohn's disease patients and 20%-30% of UC patients [2] . In UC patients with colectomy, as many as 50% will develop at least one episode of pouchitis post-operatively [34] . The rationale, types of procedures, benefits and risks of surgery are reviewed by Hwang and Varma [35] .…”
Section: Treatment For Ibdmentioning
confidence: 99%